Pengaruh Inovasi Produk, Iklan, Electronic Word of Mouth dan Dukungan Selebriti Terhadap Keputusan Pembelian Smartphone Oppo - Muhammad Saumi Andrean Nofa; Angga Ari Prasetio; Mukhroji Mukhroji (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of product innovation, advertising, electronic word of mouth and celebrity endorsement on the decision to purchase an Oppo smartphone. Current rapid technological developments have an impact on increasing consumer demand for telecommunications equipment. Smartphones or smart phones are mobile phones that have capabilities and functions that resemble computers and an example of the benefits of smartphones in terms of software is the availability of data access services. The Oppo smartphone is one of the smartphones that is popular with many people today. Product innovation is very much needed in the current era. Apart from product innovation, things that are no less important are advertising, electronic word of mouth and celebrity endorsement. This research uses a quantitative approach with conclusions drawn through statistical analysis. The sample in this study was 97 respondents. The sampling technique is non-probability sampling with accidental sampling technique. The questionnaire data collection technique uses a Likert scale. The data analysis technique uses validity tests, reliability tests, multiple linear regression tests, t tests and f tests (stimultaneous). Based on data analysis, it is known that product innovation, advertising, electronic word of mouth and celebrity endorsement have a positive influence on the decision to purchase an Oppo smartphone